MUKHIN EFREM OSIPOVICH (THE 250TH ANNIVERSARY) - Belozerov, Igor; Rozhkova, Olena (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2016)
Interesting and outstanding figure of domestic medicine on the verge of 18–19 centuries was Ephraim Iosipovich Muhin. Article describes his contributions in the formation of anatomy, physiology, traumatology, surgery, forensic medicine, hygiene, toxicology, epidemiology, etc. The scientific work of E. I. Mukhin «First Principles of bone correcting science» was the very first national guide in traumatology and orthopedics. This direction separated from the surgery. Professor is considered the founder of the national traumatology. E. I. Muhin organized work in a hospital and anyone could get help at any time for free. Professor one of the first who organized vaccination against smallpox. Many E. I. Mukhin’s students, who later became outstanding doctors, including N. I. Pirogov and I. W. Buyal’skiy, gratefully remembered his teacher. He has helped many people to get medical education, and he directed the most talented to foreign universities. In connection with the anniversary of E. I. Mukhin significant work conducted to perpetuate his memory at home, and initiated celebration «Born in the Ukraine» under the auspices of the public council of Kharkiv Regional State Administration, Ukrainian public organization named by Pirogov «Military medicine of Ukraine», Ukrainian public organization «Ukrainian Association of orthopedic trauma» and the University of Kharkiv named by V. N. Karazin.